2016
DOI: 10.1177/1049909115627425
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Palliative Care Advanced Practice Nurses Into Intensive Care Unit Teams

Abstract: Our evaluation suggests that the integration of APNs into a palliative care team for case finding may be a promising strategy, but more work is needed to determine whether reductions in cost are significant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 23 publications
1
12
0
3
Order By: Relevance
“…Other strategies for increasing early access to PCCs for patients in the ICU include a palliative care checklist for daily rounding in the ICU 11 and integration of a palliative care advanced practice nurse into the ICU. 3,14 Our overall findings are consistent with those in previous research. 14,19e26 Additionally, propensity score adjusted comparisons and stratification by timing of PCCs provide additional new insights from our data.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Other strategies for increasing early access to PCCs for patients in the ICU include a palliative care checklist for daily rounding in the ICU 11 and integration of a palliative care advanced practice nurse into the ICU. 3,14 Our overall findings are consistent with those in previous research. 14,19e26 Additionally, propensity score adjusted comparisons and stratification by timing of PCCs provide additional new insights from our data.…”
Section: Discussionsupporting
confidence: 92%
“…1e5 A recent preliminary study conducted at two hospital sites suggested that integrating an advanced practice nurse into the ICU can lead to lower costs of care for patients receiving PCCs. 14 Additional multicenter studies are needed to provide data about the impact of early PCC. This project was designed to produce and assess the impact of early delivery of PCCs in medical ICUs.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the studies demonstrate impact of the APP role through improved patient flow and clinical outcomes including reducing complications and improved patient care management with reduced time on mechanical ventilation, increased use of clinical practice guidelines, improved laboratory test use, and increased palliative care consultations, among other areas of impact. Studies also demonstrate positive financial outcomes with reduced ICU LOS, hospital LOS, (re)admission rates, and improved discharge time among others (1619, 24, 28, 3135, 37, 45, 48, 50, 51, 55, 6066, 72, 75).…”
Section: Discussionmentioning
confidence: 91%
“…One systematic review of 18 studies of APPs in acute care (15), a systematic review of 15 studies of advanced practice nursing roles in emergency and critical care settings (16), a systematic review of 29 studies of APP care on surgical services (17), a systematic review of 14 studies of NP impact on cost, quality of care, satisfaction and wait times in ED settings (18), a literature review of 47 studies on NP care on critical care services (19), a narrative review of 29 studies related to PA satisfaction (20), a literature review of 12 studies on NP use and intensivist staffing (21), a literature review of five studies focused on APP care for ICU patients (22), a systematic review of 30 studies on the impact of APP care for adult critical care patients with a meta-analysis of eight studies (23), and 44 individual studies were identified. The studies addressed a variety of APP models of care including 24/7 ICU coverage (24), and specialty practice roles including cardiovascular surgery (25–28), neuroscience (29, 30), trauma care (3139), pediatric critical care (4044), oncology care (45, 46), surgical services (17, 47), ED settings (16, 19), orthopedics (48), stroke care (30), heart failure care (49), burn care (15), aneurysmal subarachnoid hemorrhage care (50), and palliative care (51), among other areas of specialty care. Other practice models included APP led rapid response teams (52–54), critical care outreach service (55, 56), nocturnist care (50), interventionalist service (for central venous catheter placement) (57), and sepsis care team (58).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, integration of APNs into a palliative care team for case finding so as to relieve the pressure of nurses. [24] 4.1.4 Giving priority to satisfy physical and mental needs of dying patients in ICU and their families, leaving no regrets B-3. Providing care opportunities with family members before death through timely identifying deaths and arranging time and space for visits and farewells to ensure family members have no regrets.…”
Section: B-2mentioning
confidence: 99%